Serum calcium and its relationship with immunoglobulin G (IgG) levels in prepartum buffaloes from the Venezuelan humid tropics - Juan Pablo Uzcátegui-Varela; Anacelmira Urbina Andueza; Janeth Caamaño Carrero (Revista Científica)
The immune system partially recognizes specific antigens due to the role of calcium (Ca2+) as an intracellular second messenger that regulates the humoral immune response. To consider a physiological association  between serum Ca2+ levels and its modulatory effect on immunoglobulin G (IgG) synthesis before calving in dairy buffaloes (Bubalus bubalis) in southern Lake Maracaibo, Venezuela, twenty clinically healthy Murrah x Mediterranean crossbred female buffaloes with excellent body condition were considered for this study. Ten were young females of 33.6±14.15 months, with nine months of gestation and 432±44.27 kg body weight. The other ten were adult buffaloes of 563±53.6 kg body weight at nine months of gestation and reproductive history of four calvings. The sampling consisted of collecting 6 milliliters (mL) of blood by jugular venipuncture in tubes without anticoagulant; then, the serum was separated by centrifugation at 3,300 r.p.m. for 20 minutes at 25 °C using a BOECO®-Germany centrifuge. Next, 1 mL of serum was taken to determine the serological parameters under study. Ca2+ was found in the blood through the Arsenazo III method using a Selectra ProsS ELITech®- Netherlands Analyzer and, to quantify the levels of IgG; the immunoturbidimetry technique was used with the Cobas c311 Roche® Analyzer®-USA. The data were subjected to the Kruskal-Wallis nonparametric test and Spearman correlation analysis. According to the results obtained, primiparous B. bubalis females close to parturition presented serum Ca2+ levels (8.03±0.25 mg/dL) similar to multiparous buffaloes (8.07±0.7 mg/dL) adjusted to the reference range (6.05-11.98 mg/dL) for water buffaloes. In contrast, IgG in young females was higher (761.33±21.81 mg/dL) concerning adult buffaloes (735. 83±17.39 mg/dL) with no statistically significant differences (p>0.05) between groups for both variables; however, the correlation test indicated that, in first calving buffaloes, the circulating Ca2+ level is negatively associated (r=-0.56) with IgG concentration, a physiological response that was statistically different (p<0.05) concerning multiparous buffaloes (r=0.83). There is evidence of an association between serum calcium concentration and IgG levels that depends on the number of calvings, possibly because different metabolic pathways for Ca 2+ exchange determine the immune response among the categories of buffaloes included in the study. Thus, the functional significance of Ca2+ signaling for the prepartum B. bubalis immune system is just beginning to emerge.